The Power of Words: Exploring the Constructive and Destructive Forces of Language in Surah Ibrahim - Yusuf, Tajudeen (Journal of Quranic Sciences and Research, 2024)
This study provides a linguistic and communicative analysis of Surah Ibrahim (14:24–26), examining how language functions as a constructive and destructive force through Qur'anic metaphorical imagery. The verses use the metaphor of the "good tree" and the "evil tree" to illustrate the profound effects of speech on behavior and society. Through advanced linguistic frameworks, rhetorical analysis, and communication theory, this paper highlights how these metaphors reflect language's role in shaping moral values, social interactions, and psychological states. The study employed both qualitative and interdisciplinary approaches. The findings emphasize the Qur'anic perspective on the ethical implications of language, offering insights into contemporary communication practices. Positive language, like a firmly rooted tree, fosters constructive communication and strengthens societal bonds, while harmful speech leads to instability and social fragmentation. In contemporary contexts, these principles promote ethical communication, focusing on sincerity, truthfulness, and respect. Moreover, further research on cross-cultural communication could explore how these ethical guidelines apply in modern media and interpersonal relations.